Development of an Interactive Cryptographing Machine Based on Hiding Files in Files with a Library Processing Library for JavaScript on the Localhost Platform: Telekomunikasi Militer - Hasby Fajrus Shodiq; Desyderius Minggu; Ananda Herdi Akbar (Jurnal Telkommil, 2025)
Rapid technological developments are driving an increasing need for intelligent, unreadable data security. One particularly interesting approach is the Processing for JavaScript library-based steganography technique. A series of experiments implementing this technique focused on how hidden files can be embedded and re-extracted without compromising the data, disrupting the function of the hidden file, or altering the function of the host file. Through various experiments and tests, it was found that this experiment was able to maintain consistent results and could be further developed, with the hope of developing a practical, flexible, and secure data security system in the future.